Integrasi Teknologi Immersive learning Dalam Pembelajaran Sekolah Dasar - Putra, Lovandri Dwanda; Shiddiq, Ahmad Jafar; Khafi, Iqmal; Nugroho, Bagas (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2024)
The ongoing advancement of technology continues to enrich new media for creating a more engaging learning environment. Immersive learning technologies, such as Augmented Reality (AR) and Virtual Reality (VR), have transformed the educational landscape by offering increasingly interactive and in-depth learning experiences. This study aims to evaluate the effectiveness of interactive learning technologies in enhancing students' understanding and engagement in elementary schools, as well as to identify the challenges encountered when using these technologies. The method employed in this paper is a literature review to gather information and research results related to the investigated theme. The findings indicate that the use of Virtual Reality (VR) and Augmented Reality (AR) in education can improve students' motivation, conceptual understanding, and critical thinking skills. Virtual Reality (VR) allows students to experience an immersive learning environment, while Augmented Reality (AR) enriches lesson material with interactive elements that support the visualization of complex concepts. The use of immersive learning technologies in the educational context has proven to be effective and comprehensible for students and holds significant potential for enhancing the quality of education. However, it requires careful planning and support for effective implementation.